2017
DOI: 10.1128/aac.01813-16
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Modeling To Estimate the Contributions of Genetic and Nongenetic Factors to Efavirenz Disposition

Abstract: Efavirenz pharmacokinetics is characterized by large between-subject variability, which determines both therapeutic response and adverse effects. Some of the variability in efavirenz pharmacokinetics has been attributed to genetic variability in cytochrome P450 genes that alter efavirenz metabolism, such as CYP2B6 and CYP2A6. While the effects of additional patient factors have been studied, such as sex, weight, and body mass index, the extent to which they contribute to variability in efavirenz exposure is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 61 publications
1
41
1
Order By: Relevance
“…The CL/F estimates of EFV for individuals with the CYP2B6*1/*1, CYP2B6*1/*6, and CYP2B6*6/*6 genotypes were 18, 14, and 8.6 liters/h, respectively. This finding highlights the growing literature evidence that warrants a pharmacogeneticsbased dose adjustment for EFV (3,5,22,31).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The CL/F estimates of EFV for individuals with the CYP2B6*1/*1, CYP2B6*1/*6, and CYP2B6*6/*6 genotypes were 18, 14, and 8.6 liters/h, respectively. This finding highlights the growing literature evidence that warrants a pharmacogeneticsbased dose adjustment for EFV (3,5,22,31).…”
Section: Discussionmentioning
confidence: 77%
“…PK models describing the disposition of efavirenz in plasma have been reported previously (3,(10)(11)(12)(13). A single study reported a PK model comprising both the parent drug (EFV) and the metabolite (8OHEFV) in plasma after a single dose that was lower than the recommended dose of efavirenz in 17 healthy Korean male subjects (14).…”
mentioning
confidence: 99%
“…Based on current evidence ( Table ), CYP2B6 normal metabolizers (NMs) are expected to have normal efavirenz metabolism and achieve therapeutic efavirenz concentrations with standard dosing (600 mg/day). CYP2B6 IMs may experience higher dose‐adjusted trough concentrations compared with NMs, which may put these patients up to a 1.3‐fold increased risk of adverse effects . For these patients, there is a “moderate” recommendation to consider initiating efavirenz with a decreased dose of 400 mg/day.…”
Section: Drug: Efavirenzmentioning
confidence: 99%
“…The effect of genotypic differences on efavirenz concentrations, as well as the allele frequency of the major metabolizing enzyme in different race and ethnicity groups, has been described previously. 68 Population pharmacokinetic modeling has shown that weight and fat-free mass affect the clearance of efavirenz; however, the association of sex with concentration differences appears to be inconclusive. 810 …”
Section: Introductionmentioning
confidence: 99%
“…68 Population pharmacokinetic modeling has shown that weight and fat-free mass affect the clearance of efavirenz; however, the association of sex with concentration differences appears to be inconclusive. 810 …”
Section: Introductionmentioning
confidence: 99%